Penerapan Model Think Pair Share untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas II MIN 1 Pasaman - Afrianti, Dina (Journal of Development Education and Learning (JODEL), 2025)
This classroom action research aims to improve mathematics learning outcomes of second-grade students at MIN 1 Pasaman through the implementation of the Think Pair Share (TPS) cooperative learning model. The research was conducted in two cycles involving 21 students. The research instruments included learning outcome tests, student activity observation sheets, and field notes. The results showed an increase in students' average scores from 65 (pre-cycle) to 72 (cycle I) and 80 (cycle II). The percentage of learning completion also increased from 47.6% (pre-cycle) to 71.4% (cycle I) and 90.5% (cycle II). In addition to cognitive improvements, there were also increases in students' activeness, ability to cooperate, and self-confidence. Thus, the TPS model has been proven effective in improving mathematics learning outcomes in elementary schools..